Find the product of X^2+x-12/x^2-5x-6 with complete solution
1 answer:
Answer:
(x²+x-12)(x²-5x-6)= x².x²+ x².(-5x)+x²(-6)+ x.x²+x.(-5x)+x.(-6)
(-12).x²+(-12)(-5x)+(-12)(-6)
= x⁴-5x³-6x²+x³-5x²-6x-12x²+60x+72
=x⁴-4x³-23x²+54x+72
You might be interested in
Answer:
it will be C because if u multiplie -6 by 4 it will equle -24 meaning that n=-6
It is the graph of p is steeper than the graph of q.
Answer:
124*0.9=111.6
Step-by-step explanation:
Answer:
108
Step-by-step explanation:
4−22+135−9
=−18+135−9
=117−9
=108
Answer:
PSC=PTC
They are the same angle